2013
DOI: 10.2225/vol16-issue6-fulltext-13
|View full text |Cite
|
Sign up to set email alerts
|

The genetic diversity of Sardinian myrtle (Myrtus communis L.) populations

Abstract: Background:The myrtle (Myrtus communis) is a common shrub widespread in the Mediterranean Basin. Its fruit and leaves exhibit antioxidant, antibacterial and antifungal properties, and are used for their content of essential oils and for their medicinal properties, but most commonly as an ingredient in locally made liquor. The uncontrolled exploitation of natural stands has reduced both the species' geographical coverage and the size of individual populations. The selection of genotypes for controlled cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Only in recent times has the genetic variability of wild and candidate cultivar selections in Sardinia been deeply explored (Melito et al, 2013a(Melito et al, , 2014. This genetic approach highlighted the importance of the molecular markers in assessing the genetic diversity in wild accession and candidate cultivar selections.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Only in recent times has the genetic variability of wild and candidate cultivar selections in Sardinia been deeply explored (Melito et al, 2013a(Melito et al, , 2014. This genetic approach highlighted the importance of the molecular markers in assessing the genetic diversity in wild accession and candidate cultivar selections.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Previous studies on Italian (Melito et al, 2016;Agrimonti et al, 2007;Melito et al, 2013a;Melito et al, 2014) and Mediterranean myrtle populations (Bruna et al, 2007;Nora et al, 2015;Messaud et al, 2011;Serce et al, 2008;Albaladejo et al, 2009) showed that dominant and codominant molecular markers could associate genotype to a specific geographic area. In particular, AFLPs are extremely useful to assess the genetic diversity of myrtle, screening a large number of loci simultaneously without any preliminary knowledge on the genotype sequence.…”
Section: Introductionmentioning
confidence: 95%
“…Several studies conducted on Italian myrtle populations have shown that molecular markers can be successfully used to characterize natural populations (Agrimonti et al, 2007;Bruna et al, 2007;Melito et al, 2013a;Melito et al, 2016). More recently, AFLP analysis has been performed to characterize domesticated (Melito et al, 2014) and wild myrtle populations (Melito et al, 2016), respectively, in Sardinia and Sicily.…”
Section: Aflp Analysis and Population Genetic Structurementioning
confidence: 99%
See 2 more Smart Citations